Propuesta de diseño de un modelo de gestión de calidad basado en la norma iso 9001:2015 para mejorar los procesos de gestión docente en una universidad privada de la ciudad de Trujillo - Díaz Fernández, Romy Angélica (2017)
The research was conducted in Private University from Trujillo, an organization dedicated to the university education. The overall objective was to document a system of quality management based on ISO 9001:2015 for the area of Educational Quality - Teaching Management. This research was descriptive and field design was. The processes that involve Teaching Management: recruitment, selection and incorporation, teacher management and untying. The characteristics of this improvement are the standardization, the existence of indicators, matrices of responsibility and a culture of continuous improvement. To achieve the objectives, techniques used content analysis since information was collected in a systematic and objective manner and valid from various sources, direct observation and interview. The population was conformed by the processes of the university and the sample by the processes of the area of educational quality teaching management. With regard to the expected results it proceeded to elaboration of manuals of quality management, process description and procedures for a Private University, to improve the processes and the times that involve Teaching Management as well as continuous improvement of the process. 11 procedures, 47 indicators of procedures, 11 matrices of responsibility and 33 recommendations of good practices for continuous improvement were obtained. This research is oriented to study a starting point, an orientation to the principles of quality, to later implement and obtain certification.